Reply to "comment on 'Classical description of H(1s) and H∗(n=2) for cross-section calculations relevant to charge-exchange diagnostics'" - Cariatore, Nelson Daniel (2016)
In reply to the Comment of Jorge et al. [Phys. Rev. A 93, 066701 (2016)], we agree and reconfirm that the alternative classical trajectory Monte Carlo method (called hydrogenic-Z-CTMC) radial distributions for H∗(n = 2) we recently published are not stable in time. However, we show that such lack of stability which is more noticeable for H(2s) than for H(2p) is due to the initialization procedure employed and not to the hydrogenic-Z-CTMC method itself. A new set of completely stable hydrogenic-Z-CTMC calculations for H∗(n = 2) is introduced and found in very good agreement with standard microcanonical results reinforcing our previous findings. A second criticism of Jorge et al. concerning the number of components in hydrogenic-ZCTMC with n > 1 for H(1s) is shown not to have a significant impact on relative (n,l) populations in the final state.